Perivascular fibrosis and IgG4-related disease: a case report - S. Monti; G. Crepaldi; A. Peri; A. Pietrabissa; P. Morbini; F. Bobbio-Pallavicini; C. Montecucco; R. Caporali (PAGEPress Publications, 2014)
Immunoglobulin G4-related disease (IgG4-RD) is a newly recognized fibroinflammatory condition which can potentially involve any organ. Some characteristic histopathologic features with lymphoplasmacytic infiltrate, an increased number of IgG4+ cells, storiform fibrosis and obliterative phlebitis are the mainstay for diagnosis. Serum IgG4 levels often increase. We report the case of a patient with perivascular fibrotic lesions involving the aortic arch and the splenic hilum, with a surgical biopsy-proven diagnosis of IgG4-related disease. The patient is now undergoing a low-dose corticosteroid maintenance therapy without evidence of new localizations of the disease. This case highlights the need for increasing awareness and recognition of this new, emerging clinical condition.